DAMPAK PENGGUNAAN MEDIA SOSIAL TERHADAP PERGESERAN BAHASA DAERAH PADA GENERASI Z DI SMKN 1 POGALAN - Widyatama, Wahyu; Panji Hermoyo, R. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The massive use of social media among Generation Z has the potential to alter the linguistic landscape, particularly the existence of local languages. This study aims to analyze the impact of social media platform usage (TikTok, Instagram, and X) on the shift of the local language (Javanese) in the daily oral communication patterns of students at SMK Negeri 1 Pogalan. This study employed a qualitative approach with a case study design. Data were gathered through structured questionnaires, in-depth interviews with students and teachers, and direct observation of oral interactions in the school environment. The findings indicate that high social media intensity significantly shifts the frequency of using the Javanese language, especially the krama (formal) register. Short video content on TikTok and Instagram, as well as text-based trends on X, encourage students to adopt Indonesian slang, foreign terms, and mixed languages (bilingualism/code-mixing) into their real-life oral communication at school. This shift occurs due to the perception that using local languages on social media is less adaptive and less trendy. Social media acts as a primary catalyst in accelerating the erosion of local language culture among Generation Z at SMK Negeri 1 Pogalan, characterized by a decline in formal Javanese language proficiency and an increase in the use of popular internet language in real life.